The Empirical Science of Religious Education - Robbins, Mandy (Taylor and Francis, 2016)
The Empirical Science of Religious Education- Front Cover -- The Empirical Science of Religious Education -- Title Page -- Copyright Page -- Contents -- Contributors -- Preface -- Acknowledgements -- Introducing the empirical science of religious education -- Pioneers in the 1960s -- British Journal of Religious Education -- Illustrating the Jackson era -- Jackson's editorial legacy -- Into the future -- References -- Part I: Ethnographic fieldwork -- Chapter 1: Bridging the gap between young people's experience of their religious traditions at home and school: The contribution of ethnographic research -- Abstract -- Introduction -- Young Hindus' and Sikhs' school encounter with their religious tradition -- Evidence of interaction -- Discrepancies between nurture and curriculum books -- Issues raised by discrepancies -- Ethnographic process -- A curriculum series -- Conclusion -- References -- Chapter 2: Issues in the delivery of religious education to Muslim pupils: Perspectives from the classroom -- Abstract -- RE in a multi-faith society: The challenge -- Preparation for a religiously diverse society -- Teaching pupils from diverse religious backgrounds -- The Research -- Findings -- Starting points -- Spirituality -- Justice -- Note -- References -- Part II: Practitioner research and community of practice -- Chapter 3: Researching religious education pedagogy through an action research community of practice -- Abstract -- Introduction -- Background and contexts -- Process -- Research findings (Level 1) -- Critical discussion (research findings, Levels 2 and 3) -- Conclusion and recommendations -- Note -- References -- Chapter 4: 'I'm less intolerant': Reflexive self-assessment in religious education -- Abstract -- Introduction -- Pupils' reflection in religious education -- Self-assessment as assessment for learning.